Effect of Vitex agnus-castus plant on sexual function in women of reproductive age - Seyedeh Fatemeh Dalil Heirati; Roya KaboudMehri; Faraz Mojab; Shamim Sahranavard; Maliheh Nasiri; Giti Ozgoli (Mashhad University of Medical Sciences, 2020)
Introduction: It is important to pay attention to the sexual function of women of childbearing age due to long-term conflict with it and its impact on personal health, marital relations and childbearing. The phytoestrogenic effect of the Vitex agnus-castus plant on sexual function of postmenopausal women as well as in limited animal studies has been shown to improve, enhance sexual behavior and hormones, but it has not been studied in women of childbearing age. Therefore, this study was performed with aim to determine the effect of Vitex agnus-castus plant consumption on sexual dysfunction in women of childbearing age.  Methods: This double-blind clinical trial study was performed on 102 women referred to Alzahra Women's Clinic of Rasht for doing Pap smears in 2019. Eligible candidates completed the Female Sexual Function Index (FSFI) questionnaire; if they were placed in the group of sexual dysfunction and then randomly assigned to two groups of Vitex agnus-castus tablet or placebo. FSFI questionnaire was again completed after 4 weeks. Data were analyzed by SPSS software (version 21) and Chi-square, Fisher, Mann-Whitney, Independent-t and paired t-test. P<0.05 was considered statistically significant. Results: Two groups were homogeneous in terms of demographic, social and midwifery characteristics, and mean scores of total sexual function and domains were similar between the two groups before the (p≥0.05). After one month of the intervention, mean score of total sexual function and domains was not statistically significant between two groups (p≥0.05). In comparison of the scores within-group, only the score of orgasm domain was improved (p=0.02). Conclusion: There was no change in sexual function of women before and after the intervention; so it is recommended that given the mechanism of the effects of phytoestrogens and similar studies in postmenopausal women, this study be conducted over a long period of time.